Structural and Functional Changes in Aged Skin Lymphatic Vessels - Kataru, Raghu P.; Park, Hyeung Ju; Shin, Jinyeon; Baik, Jung Eun; Sarker, Ananta; Brown, Stav; Mehrara, Babak J. (Frontiers in Aging, 2022)
Lymphatic structure and function play a critical role in fluid transport, antigen delivery, and immune homeostasis. A dysfunctional lymphatic system is associated with chronic low-grade inflammation of peripheral tissues, poor immune responses, and recurrent infections, which are also hallmarks of aging pathology. Previous studies have shown that aging impairs lymphatic structure and function in a variety of organ systems, including the intestines and central nervous system. However, previous studies are mostly limited to qualitative analysis of lymphatic structural changes and quantification of intestinal collecting vessel contractile function. It is not clear whether decreased lymphatic function contributes to pathological conditions related to aging, nor how it affects the skin immune microenvironment. Further, the effects of aging on skin initial and collecting lymphatic vessels, dendritic cell (DC) migration, cutaneous lymphatic pumping, and VEGFR-3 signaling in lymphatic endothelial cells (LECs) have not been quantitatively analyzed. Here, using fluorescent immunohistochemistry and flow cytometry, we confirm that aging decreases skin initial and collecting lymphatic vessel density. Indocyanine green (ICG) lymphangiography and DC migration assays confirm that aging decreases both fluid pumping and cell migration via lymphatic vessels. At the cellular level, aging causes decreased VEGFR-3 signaling, leading to increased LEC apoptosis and senescence. Finally, we determined that aging causes decreased lymphatic production of chemokines and alters LEC expression of junctional and adhesion molecules. This in turn leads to increased peri-lymphatic inflammation and nitrosative stress that might contribute to aging pathology in a feed-forward manner. Taken together, our study, in addition to quantitatively corroborating previous findings, suggests diverse mechanisms that contribute to lymphatic dysfunction in aging that in turn exacerbate the pathology of aging in a feed-forward manner.